Transitioning from early childhood to primary education: what the practitioners say - Mangwaya, Ezron (Research Academy of Social Sciences, 2016)
Each time a learner moves from one level to another transition occurs. For instance moving from early childhood to primary school is a major step which every learner has to experience in education. If not handled appropriately transition from early childhood education to the primary school can be problematic. This study explores school heads, teachers-in-charge and early childhood education teachers’ views on factors which promote successful transition. Adopting a multiple case study design this qualitative study makes use of interviews, observation and document analysis. The study proposes factors which should be taken into account for successful transition. If these factors are not carefully considered transition from early childhood to the primary school can be traumatic.